Ketahanan Pangan Melalui Pemberdayaan Komunitas Petani dalam Meningkatkan Hasil Produksi Tani Di Nagari Kamang Tangah Anam Suku Kecamatan Kamang Magek - Wanda Fitri; Vembie Rahmana; Muhammad Fauzi (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Food security constitutes a strategic issue in sustainable development, particularly in rural areas that rely heavily on the agricultural sector. Farmers often face various challenges, including low productivity, dependence on external inputs, and vulnerability to climate change and natural disasters. This study aims to analyze efforts to enhance food security through the empowerment of farming communities to improve agricultural production using the Asset-Based Community Development (ABCD) approach. This research employs a participatory qualitative approach conducted within a farming community organized under the Jaya Makmur Farmer Group in Nagari Anam Suku Kamang Magek, Agam Regency. Data collection techniques included in-depth interviews, Focus Group Discussions (FGDs), and participatory observation. Data analysis was carried out thematically based on the stages of the ABCD approach, namely discovery, dream, design, define, and destiny. The findings indicate that the farming community possesses a range of local assets—individual, social, and physical—that had not previously been utilized optimally. Through an asset-based empowerment process, farmers were able to enhance production capacity, diversify crops, and establish a community food barn. However, the full implementation of the ABCD-based program has not yet been observed, as the empowerment process is still ongoing. Its impacts are expected to be measurable through increased agricultural yields, greater stability of household food availability, and the strengthening of social capital and farmers’ psychological well-being.